Star wars street of shadows - Reaves, Michael (Coruscant nights, 2008)
After years of waiting in the shadows, Darth Sidious is taking the first step in his master plan to bring the Republic to its knees. Key to his scheme are the Neimoidians of the Trade Federation. Then one of his Neimoidian contacts disappears, and Sidious does not need his Force-honed instincts to suspect betrayal. He orders his apprentice, Darth Maul, to hunt the traitor down. ut he is too late. The secret has already passed into the hands of information broker Lorn Pavan, which places him right on the top of Darth Maul's hit list. Then, in the labyrinthine alleyways and sewers of Coruscant, capital city of the Republic, Lorn crosses paths with Darsha Assant, a Jedi Padawan on a mission to earn her Knighthood. Now the future of the Republic depends on Darsha and Lorn. But how can an untried Jedi and an ordinary man, stranger to the powerful ways of the Force, hope to triumph over one of the deadliest killers in the galaxy?